An overview of the factors that influence coping mechanisms in hemodialysis patients - Yuniar Mansye Soeli; Rachmawaty D Hunawa; Nirwanto K Rahim; Sitti Fatimah Meylandri Arsad (Universitas Negeri Gorontalo, 2023)
Patients undergoing hemodialysis face many stressors, especially physical problems due to kidney failure. These problems often weaken the patient's adaptability. Adaptive and maladaptive coping mechanisms of patients undergoing hemodialysis can be influenced by various factors, namely age, length of time undergoing hemodialysis, self-efficacy and family support. The aim of the study was to describe the factors that influence coping mechanisms in hemodialysis patients at Prof. Dr. Aloei Saboe Hospital. The design in this study uses a descriptive research design. The population in this study were all hemodialysis patients at Prof. Dr. Aloei Saboe Hospital. The sample in the study amounted to 64 respondents with a total sampling technique. The research instrument used a questionnaire. The results of this study indicate that the coping mechanism of hemodialysis patients is mostly maladaptive as many as 33 respondents (51.6%) and the factors that influence coping mechanisms based on the length of time undergoing hemodialysis are mostly low as many as 33 respondents (51.6%), self-efficacy factor is also low as many as 33 respondents (51.6%) and the factor of family support is mostly good as many as 33 respondents (51.6%). Suggestions for nurses through the provision of nursing care can be used to monitor and improve patient education about the patient's coping mechanisms while undergoing hemodialysis.